Experiences of undergoing internet-delivered cognitive behavioural therapy for climate change-related distress: a qualitative study - Nike Lindhe; Matilda Berg; Kali Andersson; Gerhard Andersson (BMC Psychiatry)
Abstract Background Internet-delivered cognitive behavioural therapy (ICBT) has previously shown promise in effectively treating climate change-related distress. The aim of the present study was to investigate participants’ experiences of undergoing a novel ICBT program targeting psychological symptoms associated with climate change. Methods Telephone interviews were conducted with nine participants who had received eight weeks of ICBT for climate change-related distress. A semi-structured interview guide was used to gather information about participants’ experiences of undergoing treatment. Data were transcribed and analyzed using thematic analysis. Results The thematic analysis resulted in three overarching themes: (1) Same old feelings, brand new strategies, (2) Bumps in the road, and (3) Personalized climate engagement. Participants experienced that they had developed new coping strategies for handling their emotions, encountered challenges during the treatment period, and adapted their pro-environmental behaviour to their individual needs and circumstances. Conclusions The results indicate that participants were able to utilize the treatment material in different ways, resulting in a variety of emotional, cognitive, and behavioural changes. While the treatment was generally described as helpful, participants also raised some concerns regarding the treatment format. These findings can inform further development of ICBT targeting psychological symptoms associated with climate change.